Physiological- and performance-related effects of acute olive oil supplementation at moderate exercise intensity - Esquius, Laura; Garcia-Retortillo, Sergi; Balagué, Natàlia; Hristovski, Robert; Javierre, Casimiro (Springer Science and Business Media LLC, 2019)
The consumption of olive oil is associated with a diminished risk of cardiovascular disorders and mortality, but the impact of olive oil supplementation on endurance performance is still unclear. Since the beneficial effects of olive oil are observed at a systemic level, its effectiveness may not be precisely measured through the commonly registered maximal and threshold values of some physiological and performance parameters. In contrast, we suggest evaluating it through variables able to capture the coordinated behaviour of physiological systems. Thus, the aim of the current research was to assess the effect of an acute extra virgin olive oil supplementation on cardiorespiratory coordination (CRC) and performance, compared to palm oil.